Taking Stock, June 2011 : An Update on Vietnam's Recent Economic Developments - World Bank (Washington, DC, 2017)
In the last few years, Vietnam's macroeconomic situation has followed a predictable pattern. When faced with external shocks the authorities have opted to protect the country's rapid growth rate, even if it meant tolerating higher levels of macroeconomic instability. This has meant modest growth slowdowns and frequent episodes of overheating. So when the economy started to overheat in late 2010 following the delayed withdrawal of the fiscal and monetary stimulus put in place in 2009, few expected a determined response from the government to stem the ensuing macroeconomic volatility. The current episode of macroeconomic instability has been as severe as the previous overheating episode of mid-2008. The author constructed a summary measure of macroeconomic instability, Vietnam Index of Macroeconomic Stability (VIMS), based on the movement of four variables, namely nominal exchange rate, international reserves, inflation rate and nominal interest rate. Our measure shows that the degree of macroeconomic instability during the current episode did come quite close to mid-2008, but has not surpassed it yet. But unlike 2008, when the level of instability increased sharply and fell immediately, instability has persisted over a longer period of time during the current episode, from November 2010 to February 2011, exposing Vietnam's economy to a prolonged period of nervousness and uncertainty.